(untitled) (Journal of the College of Basic Education, 2024)
This research examines the concepts of synchrony and diachrony as two important elements in a dialectical duality in modern linguistic studies. Synchrony focuses on language within a specific period without considering temporary changes that occur in the language. Diachrony, on the other hand, studies a single language over time and examines the changes that occur in it. Saussure’s categorization tends towards a historical approach to the study of language, which we do not follow in this study. Instead, we shed light on the temporal movement within words, whether verbs or other lexical items containing temporal connotations. We investigate all of this and its impact on the Holy Quran, particularly in Surah Al-Zumar, analyzing its stylistic features in the text, as it constitutes a clear phenomenon in Surah Al-Zumar, as we will see through the research.